Evaluation of Hepatoprotective Activity of Flowers of â€œTagetes erecta linnâ€ - Chivde, Basavaraj v (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTIn the present study, the hepatoprotective activity of the ethanolic extract of flowers of Tagetes erecta was carried out. For the study, male wister rats weighing 200-250gm were used and divided into six group of four in each. Experimentally induced hepatotoxicity by using CCl4 /olive oil (1:1, 3ml/kg, i.p.for seven days), silymarin suspended in 0.6% c.m.c.( 100mg/kg, orally. For seven days) as standard reference and 100mg, 200mg, and 400mg/kg of ethanolic extract of flowers of plant Tagetes erecta for seven consecutive days orally followed by CCl4 injection on day seven. Pre-treatment with ethanolic extract of Tagetes erecta reduced the biochemical markers of hepatic injury like SGPT, SGOT, ALP and bilirubin levels and histopathological examination showned 200 and 400mg/kg showed hepatoprotective property. This results indicate the flower of tagetes erecta possess hepatoprotective property may be attributed to the quercetin related flavonoids present in the flower of Tagetes erecta.